You are on page 1of 47

The Fibonacci Numbers

The numbers are:

1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . .

Each Fibonacci number is the sum of the previous two Fibonacci


numbers!

Let n any positive integer. If Fn is what we use to describe the nth


Fibonacci number, then

Fn = Fn−1 + Fn−2
Trying to prove: F1 + F2 + · · · + Fn = Fn+2 − 1

We proved a theorem about the sum of the first few Fibonacci


numbers:
Theorem
For any positive integer n, the Fibonacci numbers satisfy:

F1 + F2 + F3 + · · · + Fn = Fn+2 − 1
The “even” Fibonacci Numbers

What about the first few Fibonacci numbers with even index:

F2 , F4 , F6 , . . . , F2n , . . .

Let’s call them “even” Fibonaccis, since their index is even,


although the numbers themselves aren’t always even!!
The “even” Fibonacci Numbers

Some notation: The first “even” Fibonacci number is F2 = 1.

The second “even” Fibonacci number is F4 = 3.

The third “even” Fibonacci number is F6 = 8.

The tenth “even” Fibonacci number is F20 =??.

The nth “even” Fibonacci number is F2n .


HOMEWORK

Tonight, try to come up with a formula for the sum of the first few
“even” Fibonacci numbers.
1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . .

Let’s look at the first few:

F2 + F4 = 1 + 3 = 4

F2 + F4 + F6 = 1 + 3 + 8 = 12

F2 + F4 + F6 + F8 = 1 + 3 + 8 + 21 = 33

F2 + F4 + F6 + F8 + F10 = 1 + 3 + 8 + 21 + 55 = 88

See a pattern?
1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . .

It looks like the sum of the first few “even” Fibonacci numbers is
one less than another Fibonacci number.

But which one?

F2 + F4 = 1 + 3 = 4 = F5 − 1

F2 + F4 + F6 = 1 + 3 + 8 = 12 = F7 − 1

F2 + F4 + F6 + F8 = 1 + 3 + 8 + 21 = 33 = F9 − 1

F2 + F4 + F6 + F8 + F10 = 1 + 3 + 8 + 21 + 55 = 88 = F11 − 1
Can we come up with a formula for the sum of the first few “even”
Fibonacci numbers?
1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . .

Let’s look at the last one we figured out:

F2 + F4 + F6 + F8 + F10 = 1 + 3 + 8 + 21 + 55 = 88 = F11 − 1

The sum of the first 5 even Fibonacci numbers (up to F10 ) is the
11th Fibonacci number less one.
Maybe it’s true that the sum of the first n “even” Fibonacci’s is
one less than the next Fibonacci number. That is,

Conjecture
For any positive integer n, the Fibonacci numbers satisfy:

F2 + F4 + F6 + · · · + F2n = F2n+1 − 1
Trying to prove: F2 + F4 + · · · F2n = F2n+1 − 1

Let’s try to prove this!!

We’re trying to find out what

F2 + F4 + · · · F2n
is equal to.

Well, let’s proceed like the last theorem.


Trying to prove: F2 + F4 + · · · F2n = F2n+1 − 1
We know F3 = F2 + F1 .
So, rewriting this a little:

F2 = F3 − F1

Also: we know F5 = F4 + F3 .
So:
F4 = F5 − F3

In general:

Feven = Fnext odd − Fprevious odd


Let’s put these together:
Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1

F2 = F3 − F1
F4 = F5 − F3
F6 = F7 − F5
F8 = F9 − F7
.. ..
. .
F2n−2 = F2n−1 − F2n−3
F2n = F2n+1 − F2n−1

Adding up all the terms on the left sides will give us something
equal to the sum of the terms on the right sides.
Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1

F2 = /F//3 − F1

F4 = F5 − /F//3

F6 = F7 − F5
F8 = F9 − F7
.. ..
. .
F2n−2 = F2n−1 − F2n−3
+ F2n = F2n+1 − F2n−1
Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1

F2 = /F//3 − F1

F4 = /F//5 − /F//3

F6 = F7 − /F//5

F8 = F9 − F7
.. ..
. .
F2n−2 = F2n−1 − F2n−3
+ F2n = F2n+1 − F2n−1
Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1

F2 = /F//3 − F1

F4 = /F//5 − /F//3

F6 = /F//7 − /F//5

F8 = F9 − /F//7
.. ..
. .
F2n−2 = F2n−1 − F2n−3
+ F2n = F2n+1 − F2n−1
Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1

F2 = /F//3 − F1

F4 = /F//5 − /F//3

F6 = /F//7 − /F//5

F8 = /F//9 − /F//7
.. ..
. .
F2n−2 = F2n−1 − /F//2n−3
/////

+ F2n = F2n+1 − F2n−1


Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1

F2 = /F//3 − F1

F4 = /F//5 − /F//3

F6 = /F//7 − /F//5

F8 = /F//9 − /F//7
.. ..
. .
///// − /F//2n−3
F2n−2 = /F//2n−1 /////

+ F2n = F2n+1 − /F//2n−1


/////
Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1

F2 = /F//3 − F1

F4 = /F//5 − /F//3

F6 = /F//7 − /F//5

F8 = /F//9 − /F//7
.. ..
. .
///// − ////////
F2n−2 = /F//2n−1 F2n−3

+ F2n = F2n+1 − ////////


F2n−1

F2 + F4 + F6 + · · · + F2n = F2n+1 − F1
Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1

F2 = /F//3 − F1

F4 = /F//5 − /F//3

F6 = /F//7 − /F//5

F8 = /F//9 − /F//7
.. ..
. .
///// − ////////
F2n−2 = /F//2n−1 F2n−3

+ F2n = F2n+1 − ////////


F2n−1

F2 + F4 + F6 + · · · + F2n = F2n+1 − 1
Trying to prove: F2 + F4 + · · · F2n = F2n+1 − 1

This proves our second theorem!!


Theorem
For any positive integer n, the even Fibonacci numbers satisfy:

F2 + F4 + F6 + · · · + F2n = F2n+1 − 1
The “odd” Fibonacci Numbers

What about the first few Fibonacci numbers with odd index:

F1 , F3 , F5 , . . . , F2n−1 , . . .

Let’s call them “odd” Fibonaccis, since their index is odd,


although the numbers themselves aren’t always odd!!
The “odd” Fibonacci Numbers

Some notation: The first “odd” Fibonacci number is F1 = 1.

The second “odd” Fibonacci number is F3 = 2.

The third “odd” Fibonacci number is F5 = 5.

The tenth “odd” Fibonacci number is F19 =??.

The nth “odd” Fibonacci number is F2n−1 .


1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . .

Let’s look at the first few:

F1 + F3 = 1 + 2 = 3

F1 + F3 + F5 = 1 + 2 + 5 = 8

F1 + F3 + F5 + F7 = 1 + 2 + 5 + 13 = 21

F1 + F3 + F5 + F7 + F9 = 1 + 2 + 5 + 13 + 34 = 55

See a pattern?
1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . .

It looks like the sum of the first few “odd” Fibonacci numbers is
another Fibonacci number.

But which one?

F1 + F3 = 1 + 2 = 3 = F4

F1 + F3 + F5 = 1 + 2 + 5 = 8 = F6

F1 + F3 + F5 + F7 = 1 + 2 + 5 + 13 = 21 = F8

F1 + F3 + F5 + F7 + F9 = 1 + 2 + 5 + 13 + 34 = 55 = F10
Can we come up with a formula for the sum of the first few “even”
Fibonacci numbers?
1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . .

Maybe it’s true that the sum of the first n “odd” Fibonacci’s is the
next Fibonacci number. That is,

Conjecture
For any positive integer n, the Fibonacci numbers satisfy:

F1 + F3 + F5 + · · · + F2n−1 = F2n
Trying to prove: F1 + F3 + · · · + F2n−1 = F2n
Let’s try to prove this!!

We know F2 = F1 .
So, rewriting this a little:

F1 = F2

Also: we know F4 = F3 + F2 .
So:
F3 = F4 − F2

In general:
Fodd = Fnext even − Fprevious even
Trying to prove: F1 + F3 + · · · + F2n−1 = F2n

F1 = F2
F3 = F4 − F2
F5 = F6 − F4
F7 = F8 − F6
.. ..
. .
F2n−3 = F2n−2 − F2n−4
+ F2n−1 = F2n − F2n−2

Adding up all the terms on the left sides will give us something
equal to the sum of the terms on the right sides.
Trying to prove: F1 + F3 + · · · + F2n−1 = F2n

F1 = /F//2

F3 = F4 − /F//2

F5 = F6 − F4
F7 = F8 − F6
.. ..
. .
F2n−3 = F2n−2 − F2n−4
+ F2n−1 = F2n − F2n−2
Trying to prove: F1 + F3 + · · · + F2n−1 = F2n

F1 = /F//2

F3 = /F//4 − /F//2

F5 = F6 − /F//4

F7 = F8 − F6
.. ..
. .
F2n−3 = F2n−2 − F2n−4
+ F2n−1 = F2n − F2n−2
Trying to prove: F1 + F3 + · · · + F2n−1 = F2n

F1 = /F//2

F3 = /F//4 − /F//2

F5 = /F//6 − /F//4

F7 = F8 − /F//6
.. ..
. .
F2n−3 = F2n−2 − F2n−4
+ F2n−1 = F2n − F2n−2
Trying to prove: F1 + F3 + · · · + F2n−1 = F2n

F1 = /F//2

F3 = /F//4 − /F//2

F5 = /F//6 − /F//4

F7 = /F//8 − /F//6
.. ..
. .
F2n−3 = F2n−2 − /F//2n−4
/////

+ F2n−1 = F2n − F2n−2


Trying to prove: F1 + F3 + · · · + F2n−1 = F2n

F1 = /F//2

F3 = /F//4 − /F//2

F5 = /F//6 − /F//4

F7 = /F//8 − /F//6
.. ..
. .
///// − //////
F2n−3 = /F//2n−2 F2n−4 //

+ F2n−1 = F2n − /F//2n−2


/////

F1 + F3 + · · · + F2n−1 = F2n
Trying to prove: F1 + F3 + · · · + F2n−1 = F2n

This proves our third theorem!!


Theorem
For any positive integer n, the Fibonacci numbers satisfy:

F1 + F3 + F5 + · · · + F2n−1 = F2n
So far:
Theorem (Sum of first few Fibonacci numbers.)
For any positive integer n, the Fibonacci numbers satisfy:

F1 + F2 + F3 + · · · + Fn = Fn+2 − 1

Theorem (Sum of first few EVEN Fibonacci numbers.)


For any positive integer n, the Fibonacci numbers satisfy:

F2 + F4 + F6 + · · · + F2n = F2n+1 − 1

Theorem (Sum of first few ODD Fibonacci numbers.)


For any positive integer n, the Fibonacci numbers satisfy:

F1 + F3 + F5 + · · · + F2n−1 = F2n
One more theorem about sums:

Theorem (Sum of first few SQUARES of Fibonacci numbers.)


For any positive integer n, the Fibonacci numbers satisfy:

F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1


Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

We’ll take advantage of the following fact:

For each Fibonacci number Fn

Fn+1 = Fn + Fn−1

Fn = Fn+1 − Fn−1

Fn2 = Fn · Fn = Fn · (Fn+1 − Fn−1 )

Fn2 = Fn · Fn+1 − Fn · Fn−1


Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

Let’s check this formula for a few different valus of n:

Fn2 = Fn · Fn+1 − Fn · Fn−1

n = 4:
F42 = F4 · F4+1 − F4 · F4−1

F42 = F4 · F5 − F4 · F3

32 = 3 · 5 − 3 · 2

9 = 15 − 6
It works for n = 4!
Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

Let’s check this formula for a few different valus of n:

Fn2 = Fn · Fn+1 − Fn · Fn−1

n = 8:
F82 = F8 · F8+1 − F8 · F8−1

F82 = F8 · F9 − F8 · F7

212 = 21 · 34 − 21 · 13

441 = 714 − 273 = 441


It works for n = 8!
Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

Let’s use this formula:

Fn2 = Fn · Fn+1 − Fn · Fn−1

To find out what the sum of the first few SQUARES of Fibonacci
numbers is:

F12 + F22 + F32 + · · · + Fn2 =????


Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1
We’re using:
Fn2 = Fn · Fn+1 − Fn · Fn−1

F12 = F1 · F2

F22 = F2 · F3 − F2 · F1

F32 = F3 · F4 − F3 · F2

F42 = F4 · F5 − F4 · F3
.. ..
. .
2
Fn−1 = Fn−1 · Fn − Fn−1 · Fn−2

+ Fn2 = Fn · Fn+1 − Fn · Fn−1


Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

F12 = /F//1//·//F/2/

F22 = F2 · F3 − ////////
F2 · F1/

F32 = F3 · F4 − F3 · F2

F42 = F4 · F5 − F4 · F3
.. ..
. .
2
Fn−1 = Fn−1 · Fn − Fn−1 · Fn−2

+ Fn2 = Fn · Fn+1 − Fn · Fn−1


Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

F12 = /F//1//·//F/2/

F22 = /F//2//·//F/3/ − ////////


F2 · F1/

F32 = F3 · F4 − ////////
F3 · F2/

F42 = F4 · F5 − F4 · F3
.. ..
. .
2
Fn−1 = Fn−1 · Fn − Fn−1 · Fn−2

+ Fn2 = Fn · Fn+1 − Fn · Fn−1


Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

F12 = /F//1//·//F/2/

F22 = /F//2//·//F/3/ − ////////


F2 · F1/

F32 = /F//3//·//F/4/ − ////////


F3 · F2/

F42 = F4 · F5 − ////////
F4 · F3/

.. ..
. .
2
Fn−1 = Fn−1 · Fn − Fn−1 · Fn−2

+ Fn2 = Fn · Fn+1 − Fn · Fn−1


Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

F12 = /F//1//·//F/2/

F22 = /F//2//·//F/3/ − ////////


F2 · F1/

F32 = /F//3//·//F/4/ − ////////


F3 · F2/

F42 = /F//4//·//F/5/ − ////////


F4 · F3/

.. ..
. .
2
Fn−1 = Fn−1 · Fn − F
//// · Fn−2
///////////
n−1

+ Fn2 = Fn · Fn+1 − Fn · Fn−1


Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1

F12 = /F//1//·//F/2/

F22 = /F//2//·//F/3/ − /F////////


2 · F1

F32 = /F//3//·//F/4/ − /F////////


3 · F2

F42 = /F//4//·//F/5/ − /F////////


4 · F3

.. ..
. .
2
Fn−1 =F //////·//F/n+1
//n−1 //// − F n−1 · Fn−2
///////////////

+ Fn2 = Fn · Fn+1 − ////////////


Fn · Fn−1

F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1


Our fourth theorem:
Theorem (Sum of first few SQUARES of Fibonacci numbers.)
For any positive integer n, the Fibonacci numbers satisfy:

F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1


So far:
Theorem (Sum of first few Fibonacci numbers.)

F1 + F2 + F3 + · · · + Fn = Fn+2 − 1

Theorem (Sum of first few EVEN Fibonacci numbers.)

F2 + F4 + F6 + · · · + F2n = F2n+1 − 1

Theorem (Sum of first few ODD Fibonacci numbers.)

F1 + F3 + F5 + · · · + F2n−1 = F2n

Theorem (Sum of first few SQUARES of Fibonacci numbers.)

F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1


Examples

1 + 2 + 5 + 13 + 34 + 89 + 233 + 610 + 1597 + 4181 = 6765

1+1+4+9+25+64+169+441+1156+3025+7921 = 89·144 = 12816

Now, complete this worksheet .....

You might also like